GAMBARAN HIGIENE PERORANGAN BERDASARKAN PERSEPSI POLA ASUH ANAK DI UPTD KAMPUNG ANAK NEGERI KOTA SURABAYA - Riana Bintang Rozaaqi (Universitas Airlangga, 2017)
Lack care of childs personal hygiene can cause some health problems such as diarrhea, worms, scabies, and others. Parenting contribute on the p ersonal hygiene behaviour. The aim of this study was to described childs personal hygiene based on parenting perception of children in UPTD Kampung Anak Negeri Surabaya. This study was a descriptive cross sectional study with quantitative approach. The sample was 30 f oster children with determining the sample by random sampling. Data were taking with questionnaires and interview. Instrument used in this study was questionnaires and interview guideline. Data analysis were conducted with descriptive analysis. The results was most of the foster children were 12-16 years old. Most of the foster children was in the road more than 7 months. The majority of foster children was schoolless. Most of the foster children was entered the UPTD because singing in the road. Most of the foster children had a good personal hygiene. Most of the foster children had democratic perception on parenting. The conclusion of this study is foster children that have otoriter, democratic, as well as permissive perception on parenting have good perception on personal hygiene.